SUSTAINABLE MANAGEMENT OF PEAT EXTRACTION FIELDS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Peatland self-recovery after peat extraction is restricted and without any purposeful actions, recovery of the territories is disproportionately long. The abandoned peat fields are not only worthless from the point of view of biodiversity but are also large SEG issuers. By developing an inventory of extracted peat fields, it has been concluded that there are about 18,000 ha that are not re-cultivated and for now have lost their natural functions. The peat formation in these areas and ecosystems functions are disturbed or destroyed. There are a number of potential ways of re-cultivation of degraded peatlands that can provide different types of benefits – either to carry out economic activities or to re-naturalise territories. Each of the potential types of re-cultivation is able to deliver different types of benefits. Landowners should select the most appropriate and acceptable option for re-cultivation based on socio-economic, environmental and climate change mitigation criteria. Based on the research and the results obtained, a model for the sustainable use of peat extraction fields has been developed, that provides support for the planning of further use of degraded peatlands. The developed model provides information about financial, economic and environmental benefits of implementing a particular form of re-cultivation. Developed model ensures the optimal information balance between GHG emission reductions, ecosystem service assessments and socio-economic aspects of land use. Based on the findings and using the developed model, it is possible to implement deliberative management decisions regarding degraded peatlands, evaluate potential re-cultivation costs, plan the expected financial return, assess the benefits of climate mitigation and take into account natural values.